2017
DOI: 10.1021/acsomega.7b00302
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanocluster Protection of Protein from UVC Radiation: A Model Study on Bovine Serum Albumin

Abstract: Harmful UVC (200–280 nm) radiation is entirely screened by a combination of dioxygen and ozone in the stratosphere. However, because of environmental pollution, depletion of stratospheric ozone layer is increasing alarmingly, ensuing danger of penetration of the harmful UVC through the earth’s atmosphere to reach the living world. Studies have shown that UVC radiation accelerates aging of albumin solutions along with other qualitative changes. Herein, we have used in situ grown and ex situ added gold nanoclust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…2830 Because there were several reports on protein-protected Au and Ag NCs and hence from the knowledge of biocompatibility, we have chosen Cu NCs for the present study. 3134 Steady-state and time-resolved fluorescence spectroscopy show that the Cu NCs bind to the various BSA pockets which results into different extents of PET with the MV derivatives. The fluorescence intensities and change in the excited-state lifetime of the Cu NCs provide a quantitative idea about the different domain-specific pockets in BSA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2830 Because there were several reports on protein-protected Au and Ag NCs and hence from the knowledge of biocompatibility, we have chosen Cu NCs for the present study. 3134 Steady-state and time-resolved fluorescence spectroscopy show that the Cu NCs bind to the various BSA pockets which results into different extents of PET with the MV derivatives. The fluorescence intensities and change in the excited-state lifetime of the Cu NCs provide a quantitative idea about the different domain-specific pockets in BSA.…”
Section: Introductionmentioning
confidence: 99%
“…To explore the different hydrophobic, hydrophilic, and mixed zones of BSA quantitatively, we have synthesized Cys-protected luminescent Cu NCs containing 9 Cu atoms and used photoinduced electron transfer (PET) between the Cu NCs and various methyl viologen (MV) derivatives which are well-known electron acceptors. Because there were several reports on protein-protected Au and Ag NCs and hence from the knowledge of biocompatibility, we have chosen Cu NCs for the present study. Steady-state and time-resolved fluorescence spectroscopy show that the Cu NCs bind to the various BSA pockets which results into different extents of PET with the MV derivatives. The fluorescence intensities and change in the excited-state lifetime of the Cu NCs provide a quantitative idea about the different domain-specific pockets in BSA.…”
Section: Introductionmentioning
confidence: 99%
“…A study performed using Au nanoclusters found that both in-grown and externally-grown nanoclusters provided varying benefits on the denaturing of protein structure due to UV radiation (Das & Purkayastha, 2017). The results of the study found that in-grown Au nanoclusters protected about 23%-40% of the protein structure from exchanging to the beta structure whereas external Au nanoclusters provided about 73%-82% protection (Das & Purkayastha, 2017). These results were similar to another study that used AuNPs to demonstrate that the presence of the NPs helps to decrease the inducement of secondary structures in HAS proteins from both UV radiation as well as high ambient temperature (Capomaccio et al, 2016).…”
Section: Noble Metal (Gold Silver and Platinum) Nps As Radioprotectantsmentioning
confidence: 99%
“…AuNPs help to stabilize that effect and prevent the conversion of proteins from the alpha helix to beta‐sheet structure. A study performed using Au nanoclusters found that both in‐grown and externally‐grown nanoclusters provided varying benefits on the denaturing of protein structure due to UV radiation (Das & Purkayastha, 2017). The results of the study found that in‐grown Au nanoclusters protected about 23%–40% of the protein structure from exchanging to the beta structure whereas external Au nanoclusters provided about 73%–82% protection (Das & Purkayastha, 2017).…”
Section: Radioprotectantsmentioning
confidence: 99%
“…[42][43][44] Recent progress in synthetic procedures, structures, and optical properties along with numerous applications of Au, Ag, and Cu NCs is well documented in numerous review articles. 42,[45][46][47][48][49][50][51][52] On the contrary, a thorough fundamental understanding of the light-harvesting capacities and vivid applications in the energy and electron transfer fields have not been extensively worked upon and compared to the QDs. 53,54 In this context, we have significantly contributed towards understanding the photophysical properties of MNCs and ways to manipulate them in various microenvironments.…”
Section: Introductionmentioning
confidence: 99%